Urchin and the heartstone - McAllister, Margaret (Margaret I.) (McAllister, Margaret (Margaret I.) Mistmantle chronicles, 2006)
Urchin and the other inhabitants of Mistmantle look forward to a time of peace with the coronation of Crispin the squirrel, but the arrival of a storm-ravaged ship with a delegation from the island of Whitewings not only delays the ceremony but sends Urchin on a perilous journey that changes his life forever.